2017
DOI: 10.1155/2017/4641203
|View full text |Cite
|
Sign up to set email alerts
|

Walking Cadence to Exercise at Moderate Intensity for Adults: A Systematic Review

Abstract: Background. Most adults choose walking as a leisure activity. However, many do not reach the international physical activity guidelines for adults, which recommend moderate intensity aerobic activity for at least 150 minutes/week in bouts of 10 minutes. Purpose. This systematic review provides an update on the walking cadence required to reach moderate intensity in adults and older adults, identifies variables associated with reaching moderate intensity, and evaluates how walking cadence intensity should be me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 41 publications
(94 reference statements)
0
23
1
Order By: Relevance
“…The discrepancy is most apparently due to a combination of differences in sample ages and employed definitions of moderate intensity; the need for a maximum fitness test to establish a relative intensity index makes the Serrano approach less practical for non-research purposes (ie, public health applications). A higher cadence might be required for older adults to achieve moderate intensity, 33 however, our findings do not support this suggestion, at least in terms of absolutely defined moderate intensity. While older adults have the capacity to walk above 100 steps/min in both laboratory and free-living setting, this does not imply that older adults require a higher cadence to achieve moderate intensity.…”
Section: Discussioncontrasting
confidence: 91%
“…The discrepancy is most apparently due to a combination of differences in sample ages and employed definitions of moderate intensity; the need for a maximum fitness test to establish a relative intensity index makes the Serrano approach less practical for non-research purposes (ie, public health applications). A higher cadence might be required for older adults to achieve moderate intensity, 33 however, our findings do not support this suggestion, at least in terms of absolutely defined moderate intensity. While older adults have the capacity to walk above 100 steps/min in both laboratory and free-living setting, this does not imply that older adults require a higher cadence to achieve moderate intensity.…”
Section: Discussioncontrasting
confidence: 91%
“…They found that individuals with IC spent less time walking and took fewer steps, particularly at medium to high cadence levels. A high cadence level of walking is equivalent to moderate-intensity activity [ 19 ], and a moderate cadence level is considered to be equivalent to low-intensity activity. Thus, it is considered that their study supported our result.…”
Section: Discussionmentioning
confidence: 99%
“…The PiezoRx thresholds for monitoring MVPA were set as follows: 100/120, 110/130, adjusted for height, and adjusted for height+fitness ( Table 1 ). The PiezoRxs thresholds that were set at 100/120 and 110/130 were based on the current literature that consistently showed that 100-110 spm is equal to ~3 METs (ie, 10.5 mL/min/kg) and that 120-130 spm is equal to ~6 METs (ie, 21 mL/min/kg) in adults [ 8 - 11 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%